Scheme iconografice consacrate Adormirii Maicii Domnului din colecţia Muzeului Naţional de Istorie a Moldovei / Iconographic patterns of the Dormition of the Mother of God in the collection of the National Museum of History of Moldova - Adelaida Chiroşca (Tyragetia, 2015)
The theme of the Dormition is reﬂected in the ﬁve icons from the collection of the National Museum of History of Moldova. Feast of the Dormition of the Mother of God, falling on August 15, is celebrated for a long time; according to some sources, it was oﬃcially established in 582. The canonical composition of the icons of the Theotokos was formed after the restoration of the veneration of icons, when the Church overcome heresy and consolidated the basic theological provisions. Initially the scenes were laconic, with a small number of characters; thereafter these iconographic compositions develop into complex patterns with a variety of characters and attributes. Icons of the Dormition from the museum's collection belong to the 18th early 20th centuries, and most of them represent the traditional iconographic patterns arranged both horizontally and vertically.